Literary biography: narrative features - Cherkashyna, Tetiana (Accents and Paradoxes of Modern Philology, 2017)
The article is devoted to the study of narrative features of the literary-biographical prose. Literary biography is the one of structural-thematic variants of the documentary literature. It consists of several subspecies which differ by the main subject of the image, the completeness of the life path of the outstanding personality, the degree of interest to the creative heritage of the main character, the dominant aspect, the veracity of the playback image of the outstanding personality.Literary-biographical text is a system that consists of a main text and a peritext. The peritext is secondary to the main text and it performs an auxiliary function in the perception and interpretation of the main text. The peritext consists of three main parts: pretext (name (alias) of the author, title, subtitle, dedication, epigraph to the entire work, Preface), pagetext (the epigraphs to parts, books, chapters; internal and footnotes; internal headers) and aftertext (notes after text, epilogue, afterword, marking the date and place of writing works, reviews, apps, content).The main text of literary biography is constructed for well-established schemes. Different types of literary-biographical writing have their narrative and structural features. Among the leading types are distinguished content-semantic literary biographies (plot-event, associative-psychological) and formalized one.